PENGARUH KARAKTERISTIK INDIVIDU, KOMPETENSI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. GAPURA ANGKASA CABANG DENPASAR - Ni Made Suardani; I Gede Gama; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Gapura Angkasa, Denpasar branch is one of the Ground Handling companies that serves passenger services while on land and loading and unloading operations in Indonesia. Examples of services provided are passenger check-in services, boarding, baggage handling, aircraft cleaning, special passenger assistance, loading and unloading of cargo, and services for all types of aircraft. To achieve company goals, the company tries to achieve optimal employee performance. The purpose of this study is to determine the effect of individual characteristics, competence and organizational culture partially and simultaneously on employee performance at PT. Gapura Angkasa, Denpasar branch. Data collection using a questionnaire, the number of samples used was 81 people. using the proportional sampling method. The data analysis technique uses multiple linear regression. Hypothesis testing is done using the F test and t test.The results showed that individual characteristics had a positive and significant effect on employee performance. Competence has a positive and significant effect on employee performance. Organizational culture has a positive and significant effect on employee performance.